Tactics of staged treatmentofexacerbated chronic generalized catarrhal gingivitis - Mashchenko I.S.; Kuznyak N.B.; Shostenko A.A. (Medičnì Perspektivi, 2016)
The paper presents the results of a comparative study of features of gingival tissues microbiocenosis and local immunity in 60 patients with chronic and exacerbated chronic generalized catarrhal gingivitis. We found that in patients with exacerbated generalized catarrhal gingivitis there exist more significant differences in terms of local humoral immunity as compared with a group of patients with chronic manifestation of the disease, characterized by a large decrease in levels of sIgA and IgM and to a lesser extent, an increase in IgG. It was established that conditionally-pathogenic streptococcal microflora leads in the etiology of chronic generalized catarrhal gingivitis and staphylococcus and fungi of the genus Candida play the dominant role in formation of exacerbations of inflammation in the gingival tissue.